Youth as Creative Development Resource: How does Social Environment Unlock Youth’s Creativity and Creativepreneurial Intention? - Suryani, Adi; Soedarso; Windiani; Hanoraga, Tony; Harmadi, Sonny Harry Budiutomo; Setyaningsih, Yuni (Indonesian Journal of Development Studies, 2022)
Youth can be invaluable creativepreneurs who bring about positive community changes. Their young age, dynamics and high enthusiasm can potentially boost their capacity to encourage community development. Moreover, recent digital technology and globalization provide fertile environment for youth to unleash their creative ideas and choose creativepreneurs as promising career. The study aims to examine social aspects which may facilitate youth potential creativity and develop entrepreneurial passion. The study is extracted from a community service program aimed at increasing competencies of Karang Taruna Karang Rejo Sawah, Surabaya. The data are collected through direct observation during the workshop session. The study finds that social environment can stimulate youth’s creativity through several ways. The first way is through youth social organization from which young people learn how to be creative, build social interaction, engage in non-formal education. The second way is through social inspiration from which youth can obtain or get motivation to start their own business by acknowledging successful and inspiring creativepreneurs’ sagas, creative products and inspiring messages or experiences. Successful creativepreneurs’ painful and rewarding experiences may strengthen youth’s creativepreneurship mentality. The third way is through partnership from which young people relate themselves with outside world and explore their development opportunities.